"Listen Then, or, Rather, Answer": Contemporary Challenges to Socratic Education. Issue 1 (February 2015) - Fullam, Jordan
Abstract The popularity of Jacques Rancière in recent work in educational philosophy has rejuvenated discussion of the merits and weaknesses of Socratic education, both in Plato's dialogues and in invocations of Socrates in contemporary educational practice. In this essay Jordan Fullam explores the implications of this trend through comparing Rancière's educational thought to an analysis of the relationship between dialectic and stultification in Plato's Republic. This task clarifies what is useful in the recent wave of scholarship that brings Rancière's work to bear upon Socratic education, and what we might redeem in the practice of teaching that Plato assigns to the character of Socrates in the Republic. Fullam also draws on the educational literature on Socratic education to provide further context to explore the usefulness of both Rancière and Socrates for contemporary teaching.